Urban native bee assemblages and the impact of the introduced European honeybee on plant-pollinator networks in the southwest Australian biodiversity hotspot - Prendergast, Kit Stasia (Curtin University, 2020)
The thesis of Kit Prendergast addressed impacts of urbanisation and introduced honeybees on native bees in southwest Australia. Additionally, efficacy of bee survey methods were evaluated. The study found remnant bushland, with high proportions of native flora, was of greater importance for supporting native bee populations, species, and pollinator networks, compared with residential gardens. Honeybees occupied distinct positions in pollinator networks, and altered network properties, with context-dependent impacts on native bees.